Thermal characterization and tomography of carbon fiber reinforced plastics using individual identification technique; Materials Evaluation; Vol. 54, iss. 5 - Vavilov V. P. Vladimir Platonovich; Grinzato E.; Bison P.G.; Marinetti S.; Bressan C. (1996, 1996)
A method for thermal characterization of defect depth and thickness using individual inversion functions is described. Experimental results are obtained with standard carbon fiber reinforced plastic specimens which contained Teflon inserts and impact damage. Accuracy in determining defect dimensions was about 10 percent for defect depth and 33 percent for defect thickness. A technique to synthesize images of defect parameters is proposed. Thermal tomography advantages in analyzing defect in-depth propagation are illustrated.